2022
DOI: 10.1111/his.14780
|View full text |Cite
|
Sign up to set email alerts
|

Refining the definition of HER2‐low class in invasive breast cancer

Abstract: Refining the definition of HER2-low class in invasive breast cancerBackground: Emerging evidence indicates that breast cancer (BC) patients whose tumours express HER2 protein without HER2 gene amplification (HER2-low), can benefit from antibody-drug conjugates (ADC). However, the current definition of HER2-low BC remains incomplete with low rates of concordance. This study aims to refine HER2-low definition with emphasis on distinguishing HER2 score 0 from score 1+ to identify patients who are eligible for ADC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…The ANN model configured HER2 IHC score 1 + as membranous staining in invasive cells either as faint intensity in ≥20% of cells regardless of the circumferential completeness, weak complete staining in ≤10%, weak incomplete staining in >10% and moderate incomplete staining in ≤10%. This model showed statistical significance with Oncotype DX scores and a perfect intra- and inter-observer agreement (kappa value = 0.8 and 0.9, respectively) ( Atallah et al, 2022 ). Such methodologies have shown promising outcomes for a more accurate and reproducible HER2-low assessment compared to the currently available methods.…”
Section: Novel Complementary Methodologies and Future Directionsmentioning
confidence: 90%
See 2 more Smart Citations
“…The ANN model configured HER2 IHC score 1 + as membranous staining in invasive cells either as faint intensity in ≥20% of cells regardless of the circumferential completeness, weak complete staining in ≤10%, weak incomplete staining in >10% and moderate incomplete staining in ≤10%. This model showed statistical significance with Oncotype DX scores and a perfect intra- and inter-observer agreement (kappa value = 0.8 and 0.9, respectively) ( Atallah et al, 2022 ). Such methodologies have shown promising outcomes for a more accurate and reproducible HER2-low assessment compared to the currently available methods.…”
Section: Novel Complementary Methodologies and Future Directionsmentioning
confidence: 90%
“…The findings of such trials could contribute to the understanding of clear-cut limits of HER2 expression required for ADC treatment strategy using the available diagnostic techniques ( Wu et al, 2023b ; Fan and Xu, 2023 ). Yet, to develop a robust definition of HER2-low, the number of recruited patients in such randomized clinical trials needs to be amplified ( Atallah et al, 2022 ). Recruitment of further diagnostic approaches with a more precise cut-off could facilitate the detection of patients suitable for targeted therapies.…”
Section: Novel Complementary Methodologies and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the recent development of HER2-directed antibody–drug conjugates [ 11 ], the correct classification of these cases is gaining importance, as it may change the clinical management of the patients. In this regard, a recent study by Atallah et al [ 27 ] suggests new refined score patterns to distinguish HER2 0+ and HER2 1+ tumors, which correlates with mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, on the contrary, in a retrospective analysis of 410 patients with lymph node‐negative BC who did not receive adjuvant therapy from 1985 to 2000, scholars found that patients with low HER2 expression had significantly longer DFS and OS, and HER2 status was an independent prognostic factor 34 . In addition, HER2‐low, compared to HER2‐zero, has also been reported as an adverse prognostic factor due to its association with metastases (axillary lymph node metastases, 35 brain metastases 36 ).…”
Section: Clinicopathological Features Of Her2‐low/zero Breast Cancermentioning
confidence: 99%